Analisis Kemampuan Komunikasi Matematika Siswa SD dalam Menyelesaikan Masalah Matematika - Utomo, Fajar Hendro (Jurnal Tadris Matematika, 2019)
This study aims to analyze communication skills in solving mathematical problems. This research is qualitative research. The subjects of the research is the Islamic Elementary School students of Quran Al Bahjah Tulungagung. Determination of subjects using purposive sampling based on communication skills and solving mathematical problems. The instrument of this research is in the form of mathematical problem solving test questions and interview sheets. Data collection techniques are done by collecting data from written tests and student interviews. The results of this study are 1) the stage of understanding the problem, the subject understands the problem well and is able to express mathematical ideas verbally and written, able to explain mathematical representations made; 2) the stage of planning a strategy for solving a story problem, the subject can explain the plan to solve the story problem that is done and have the ability to express mathematical ideas verbally and written, able to explain mathematical representations made and able to explain the relationship of ideas in solving problems; 3) the stage of implementing a settlement strategy, the subject is sure of the results done and can show that the answer is correct and able to express written and oral mathematical ideas; and 4) at the re-examination stage, the subject re-checks the answers obtained and is able to express mathematical ideas verbally and written.